A three-dimensional porous wood-based monolithic column and preparation method thereof
Wood-based monolithic chromatography columns address the limitations of traditional monolithic columns by providing a stable, efficient, and cost-effective solution for biomacromolecule separations through chemical modification and functional ligand integration.
Patent Information
- Application Number
- CN202211564064.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-07
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-12-07
AI Technical Summary
Existing monolithic columns face challenges such as uncontrollable pore size, non-uniform through-holes, high back pressure, reduced column efficiency, and low mechanical strength, particularly in large-scale biomacromolecule separations, limiting their effectiveness and stability.
Utilizing wood as a stationary phase, chemically modifying its surface to connect functional ligands, and integrating it into chromatographic columns to form three-dimensional porous wood-based monolithic columns suitable for various chromatography modes.
The wood-based monolithic columns provide enhanced mechanical strength, uniform pore structure, and efficient mass transfer, reducing separation time and costs while maintaining high resolution and stability for biomacromolecule separations.
Smart Images

Figure CN116159341B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of separation analysis, and in particular relates to a three-dimensional porous wood-based integral column and a preparation method thereof. Background Art
[0002] Due to the complexity of the environment in which biomass is located and the extremely high requirements for product stability, the cost of the separation process of biological products often accounts for more than 70% of the total production cost. Chromatography has become the most frequently used separation and purification method in the large-scale production of pharmaceutical proteins due to its high separation accuracy, mild separation conditions, simple operation and high repeatability. Monolithic columns (also known as monolithic columns, the English name is Monolithic Column) are a new generation of chromatographic stationary phases after traditional solid particle matrices. Its characteristics are that it has both small diffusion pores and large through-holes, which can accelerate the mass transfer of fluids and shorten the separation time. Within a certain range, the increase in flow rate will not significantly reduce the resolution, especially in the separation of biomacromolecules, viruses, bacteria and particles. It presents very good prospects. However, due to technical reasons such as the preparation method and porogen of monolithic columns, there are some limitations, such as: the pore size of monolithic columns is difficult to control; when synthesizing large-sized monolithic columns, the non-uniformity of through-holes will be aggravated, the back pressure is too large, and the column efficiency is reduced; the mechanical strength is low; there are problems such as lack of diffusion pores. Using wood as a natural monolithic column, its unique hierarchical structure and porous properties can successfully replace the current monolithic column matrix and become a new chromatographic column stationary phase.
[0003] The unique pore structure of wood is very conducive to the flow of fluids, and it can also absorb and intercept tiny particles in the fluid. In addition, it is green, lightweight, tough, impact-resistant, and renewable, so it has great potential in the field of biomass separation and purification. One of the advantages of wood as a protein separation matrix is its composition. The main components of wood are cellulose, hemicellulose, and lignin. Both cellulose and hemicellulose are composed of carbohydrates, and lignin is an aromatic compound. Therefore, wood contains abundant active groups such as hydroxyl, phenolic hydroxyl, and carboxyl groups that can be used for modification or direct adsorption. The active groups in wood can react with anhydrides, polycarboxylic acids, acyl chlorides, isocyanates, epoxy compounds, aldehydes, and silane compounds to form covalent bonds. Another advantage of wood is its natural hierarchical structure. The sizes of the various levels of wood structures span multiple orders of magnitude, from macroscopic meters to microscopic nanometers. In the pore structure of wood, especially coniferous wood, its tracheids account for 90%-95% of the volume of xylem cells, playing a supporting and conducting role in wood. The "natural channels" formed by these large-diameter tracheids can be used as "through holes" in wood-based monolithic chromatography columns. Using wood as a monolithic column material does not require complex synthesis steps to form through holes to prepare monolithic columns, effectively avoiding the adverse effects of porogens in monolithic columns on through holes. In addition, wood also has good mechanical properties and toughness. Using it as a monolithic column will have excellent mechanical properties and compressive resistance, good biodegradability, durability and low cost.
[0004] Cut the wood into the desired shape, such as cylinders or discs, and then modify it directly or remove impurities, lignin and other chromogenic groups on the wood surface through delignification treatment. Modify it and couple different ligands on the basis of maintaining its structural stability, and design monolithic columns of various modes, such as ion exchange chromatography, affinity chromatography, hydrophobic chromatography, and mixed mode chromatography. The new three-dimensional porous wood-based monolithic columns prepared by functionalization can purify biological substances, remove pollutants, etc., which undoubtedly has a significant and positive significance for ecological protection, resource recovery and reuse. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a three-dimensional porous wood-based monolithic chromatography column. In more detail, the present invention uses wood as a stationary phase and obtains a wood-based monolithic column that can be applied to affinity chromatography, ion exchange chromatography, hydrophobic chromatography, normal phase chromatography, reverse phase chromatography, mixed mode, chiral separation chromatography and the like by modifying the wood as a stationary phase.
[0006] The technical solution of the present invention is as follows:
[0007] The present invention provides a method for preparing a three-dimensional porous wood-based monolithic column. The specific synthesis steps of the preparation method are as follows: using wood as a stationary phase, modifying its pore surface by chemical methods, allowing its surface to be connected with a functional ligand (also called a ligand), and then placing it in an empty chromatographic column for substance separation.
[0008] The characteristic structure of the preparation of the three-dimensional porous wood-based monolithic column of the present invention is
[0009] [W]-(A)-(B)
[0010] in:
[0011] [W] stands for wood;
[0012] (A) is the middle arm, used to connect wood and functional ligand;
[0013] (B) is a functional ligand that can interact with the target substance through specific binding force or non-specific binding force.
[0014] Among them, (A) is a non-essential structure, and the whole column can also be presented in the [W](B) structure.
[0015] The invention comprises a chromatographic column tube sleeve and a stationary phase, wherein the stationary phase is natural wood or delignified wood.
[0016] The wood material of the present invention includes coniferous wood or broadleaved wood, preferably coniferous wood.
[0017] The present invention adopts a sodium hypochlorite method, a chlorite method, a sulfite method, a lignin in-situ modification method or an enzyme treatment method for wood delignification treatment.
[0018] The delignification degree of the delignified wood in the present invention is preferably such that the wood can still maintain its original three-dimensional porous structure.
[0019] The three-dimensional porous wood-based monolithic column and its preparation method described in the present invention, the intermediate arm is combined with the hydroxyl or carboxyl group on the surface of the inner pores of natural wood or delignified wood through chemical reaction, and the combining method includes but is not limited to surface grafting polymerization (grafting-from), direct modification of small molecule compounds or macromolecular polymers (grafting-to), monomer copolymerization grafting (grafting-through) and other methods to combine the intermediate arm with the wood, modify the interior of the wood, improve the shortcomings of the wood or enhance the advantages.
[0020] In the method for preparing a three-dimensional porous wood-based integral column provided by the present invention, the intermediate arm includes but is not limited to a silane coupling agent, glutaraldehyde, epichlorohydrin, dextran, agarose, cellulose, polyethylene glycol, a functional monomer, and the like.
[0021] The silane coupling agent in the present invention includes but is not limited to vinyl triethoxysilane (A-151), γ-aminopropyl trimethoxysilane (KH540), γ-aminopropyl triethyloxysilane (KH550), 3-glycidyloxypropyl trimethoxysilane (KH560), γ-methacryloxypropyl trimethoxysilane (KH570), and N-β-aminoethyl-γ-aminopropyl methyl dimethoxysilane (KH602).
[0022] The polyethylene glycol in the present invention includes two-arm polyethylene glycol, four-arm polyethylene glycol, eight-arm polyethylene glycol and branched polyethylene glycol, and its molecular weight is 120-100000 KD.
[0023] The functional monomers in the present invention refer to unsaturated, cyclic or low molecular weight compounds containing two or more functional groups, including but not limited to styrene, methyl styrene, acrylamide, methacrylamide, N-isopropylacrylamide, glycidyl methacrylate, butyl methacrylate, and N-allyl dimethylamine.
[0024] Functional ligands in the present invention include but are not limited to affinity ligands, hydrophobic ligands, ion exchange types, chiral resolving ligands, mixed mode ligands, such as protein A, Cibacron blue, diethylaminoethyl chloride hydrochloride, 3-sulfonyl methacrylate potassium salt, metal Ni ions, n-butyraldehyde, vancomycin, Oligo (dT), 4-mercaptoethylpyridine, amphetamine, N-hexylamine and N-phenyl-N-methylethanolamine.
[0025] The shape of the wood-based integral column includes but is not limited to a cylinder, a disk, a rectangle, a square, and a cone, preferably a cylinder or a disk. The wood-based integral column is a whole piece of wood or a plurality of wood-based blocks stacked together.
[0026] The wood-based monolithic column can be used for affinity chromatography, ion exchange chromatography, hydrophobic chromatography, normal phase chromatography, reverse phase chromatography, mixed mode chromatography, and chiral separation chromatography.
[0027] When designing the monolithic column, the mobile phase flow direction can be consistent with or perpendicular to the direction of the tracheids in coniferous wood (or the vessels in hardwood). When used for separation of biomacromolecules, the mobile phase flow direction is preferably consistent with the direction of the tracheids in the wood. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the synthesis process of the wood-based monolithic separation column;
[0029] Figure 2 This is a scanning electron microscope image of a polymer wood-based monolithic column;
[0030] Figure 3The reaction flow chart of the diethylamino anion column for modifying delignified wood chips with KH560 as the intermediate arm;
[0031] Figure 4 This is the BSA adsorption isotherm curve of the DEAE wood-based monolithic separation column in Example 2. DETAILED DESCRIPTION
[0032] The following examples are given to describe the present invention in detail, but are not intended to limit the present invention. The scope of the present invention is defined by the claims.
[0033] Embodiment 1:
[0034] Cut Pinus sylvestris wood into wood chips with a diameter of 2 cm and a height of 3 mm; mix 24 mL of functional monomer glycidyl methacrylate (GMA), 16 mL of cross-linking agent ethylene glycol dimethacrylate (EDMA), 54 mL of cyclohexanol, 6 mL of dodecanol, and 1 g of benzoyl peroxide (BPO), ultrasonically treat at room temperature for 30 min, then pass nitrogen for 15 min to remove dissolved oxygen in the solution, and leave it at 4°C overnight; soak the wood chips in the mixed solution and let it stand at 4°C overnight, then pass nitrogen for 15 min, seal it and place it in a water bath at 55°C for thermal initiation polymerization for 24 h. After the reaction is completed, wash the wood chips with a large amount of methanol and deionized water and then dry them; immerse the above wood chips in 50 mL of 1 mM potassium salt solution of 3-sulfonic acid propyl methacrylate (the pH of the solution is adjusted to 0.5 with 0.5 MH2SO4), stir the reaction at 30°C for 20 h, and then add 5 mL 1 mg / mL cerium ammonium nitrate aqueous solution was fully shaken at 45°C for 15 hours. After the reaction, it was repeatedly washed with deionized water and then freeze-dried to obtain a strong cationic wood-based integral separation column.
[0035] Embodiment 2:
[0036] New Zealand radiata pine wood was cut into cylinders with a diameter of 2 cm and a height of 1 cm; the cut wood was immersed in a 7% sodium hypochlorite solution and stirred at room temperature for 5 hours, and the wood was repeatedly washed with deionized water and freeze-dried; the delignified wood was immersed in a 6% KH560 solution (v / v, 95% ethanol solvent) and stirred at room temperature overnight, and then the unbound KH560 was washed with deionized water and freeze-dried again; the modified wood was placed in a 0.5M Na2CO3+1M NaCl, pH 11.5 solution for 5 hours, washed with deionized water, and then placed in 50g / L 2-diethylaminoethyl chloride hydrochloride (DEAE-Cl), reacted at 60°C for 15 hours, and the unreacted ligand was washed with deionized water and then freeze-dried to obtain a DEAE weak anion wood-based chromatographic column.
[0037] Embodiment 3:
[0038] The spruce wood was cut into cylinders with a diameter of 2 cm and a height of 5 cm; the cut wood was immersed in a 14% sodium hypochlorite solution and stirred at room temperature for 3 hours, the wood was repeatedly washed with deionized water, and then freeze-dried; the delignified wood was immersed in a 6% KH560 solution (v / v, 95% ethanol solvent) and stirred at room temperature overnight, then the unbound KH560 was washed with deionized water, and then freeze-dried again; the modified wood was placed in 50 mL of a 10 mg / mL Cibacron blue solution, 4 g of NaCl was added, mixed, and oscillated in a water bath at 45° C. and 170 rpm for 3 hours to allow the pigment to fully enter the interior of the wood, 5 mL of a 1M NaOH solution was added to the mixture and continued to oscillate for 20 hours to allow the reaction to proceed fully, and after the reaction was completed, the unreacted ligand was washed with deionized water and then freeze-dried to obtain an affinity pigment wood-based integral separation column.
[0039] Embodiment 4:
[0040] The spruce wood was cut into discs with a diameter of 2 cm and a height of 3 mm; the cut wood was immersed in a mixed solution of 5 mL 1M NaOH solution, 2.5 mL epichlorohydrin and 5 mL dimethyl sulfoxide, activated in a constant temperature water bath oscillator at 170 rpm at 25°C for 3 hours, and repeatedly rinsed with deionized water to remove residual epichlorohydrin, thereby obtaining activated wood chips; the activated wood chips were immersed in a 2 mg / mL methanol solution of protein A, shaken in a water bath at 40°C for 16 hours, and repeatedly washed with 80% methanol by volume after the reaction was completed; then the wood column was transferred to 1M ethanolamine (pH 8) and kept at 50°C overnight; finally, the wood column was thoroughly rinsed 3 times with 1M Tris-HCl+0.5M NaCl buffer (pH 8) and freeze-dried to obtain an affinity wood-based integral separation column.
[0041] Embodiment 5:
[0042] The radiata pine wood was cut into cylinders with a diameter of 2 cm and a height of 5 cm; the cut wood was immersed in a 14% sodium hypochlorite solution, stirred at room temperature for 3 hours, and the wood was repeatedly washed with deionized water and freeze-dried; the delignified wood was immersed in 100 mL of deionized water, heated and stirred at 70°C for 4 hours, and then a 10% glutaraldehyde aqueous solution was added, and the heating and stirring were continued for 1 hour, and then the deionized water was repeatedly washed and freeze-dried; the glutaraldehyde-modified wood was immersed in 50 mL of n-butyraldehyde (pH 6.0), stirred at room temperature for 10 hours, and then the deionized water and anhydrous ethanol were repeatedly washed, and freeze-dried to obtain a wood-based integral hydrophobic separation column.
[0043] Embodiment 6:
[0044] Radiata pine wood was cut into discs with a diameter of 2 cm and a height of 3 mm. The cut wood was immersed in a mixed solution of 5 mL 1 M NaOH solution, 2.5 mL epichlorohydrin and 5 mL dimethyl sulfoxide, activated in a constant temperature water bath oscillator at 170 rpm for 3 h at 25 ° C, and repeatedly rinsed with deionized water to remove residual epichlorohydrin, thereby obtaining activated wood chips. The activated wood was placed in 20 mL 300 mg / mL dextran T40 solution and shaken in a constant temperature water bath oscillator at 170 rpm for 1 h to allow Dextran T40 to evenly diffuse into the wood pores. Subsequently, 6 mL 0.8MNaOH, 40mg sodium borohydride, and react at 30℃ for 15h, and wash repeatedly with deionized water after the reaction; 1g of trimesic acid is placed in 10mL of thionyl chloride, react at 60℃ for 6h, and then evaporate to remove the solvent, then add 10ml of anhydrous N,N-dimethylformamide and 1.2g of vancomycin and react at 80℃ for 12h. After the reaction, evaporate the obtained product to remove N,N-dimethylformamide and obtain carboxylated vancomycin; the carboxylated vancomycin obtained in the above experiment and the modified wood are placed in dimethyl sulfoxide solvent, stirred at room temperature for 48h, and after the reaction, repeatedly washed with deionized water to obtain a wood-based monolithic chromatographic column loaded with vancomycin.
[0045] Embodiment 7:
[0046] The larch wood was cut into round pieces with a diameter of 2 cm and a height of 3 mm; the cut wood was immersed in a mixed solution of 5 mL 1M NaOH solution, 2.5 mL epichlorohydrin and 5 mL dimethyl sulfoxide, activated in a constant temperature water bath oscillator at 170 rpm at 25°C for 3 hours, and repeatedly rinsed with deionized water to remove residual epichlorohydrin, thereby obtaining activated wood chips; 50 mL of pH 7 iminodiacetic acid solution and 50 mL of pH 9.5 MaHCO3 buffer were added to the activated wood chips, and the reaction was shaken at 37°C and 200 rpm for 24 hours, and then repeatedly washed with deionized water; the wood chips were then added to 50 mL of 0.1M NiSO4 solution and immersed for 3 hours, and then repeatedly washed with deionized water, and freeze-dried to obtain a metal affinity wood-based integral separation column.
[0047] Embodiment 8:
[0048] The spruce wood was cut into cylinders with a diameter of 2 cm and a height of 5 cm; the cut wood was soaked in a 14% sodium hypochlorite solution, stirred at room temperature for 3 hours, and the wood was repeatedly washed with deionized water and then freeze-dried; the delignified wood was soaked in a 6% KH560 solution (v / v, 95% ethanol solvent) and stirred at room temperature overnight, and then the unbound KH560 was washed with deionized water and freeze-dried again; the silanized wood chips were mixed with 50 mL of a 30% aminopolyethylene glycol 2000 aqueous solution, heated at 60°C for 10 hours, and repeatedly washed with deionized water after the reaction; the reacted wood chips were then incubated with 30 mL of a 10 mg / mL Oligo(dT)18 solution at pH 8, 37°C, and 200 rpm shaking for 24 hours, and after the reaction, they were repeatedly washed with deionized water and freeze-dried to obtain an Oligo(dT) wood-based monolithic separation column.
[0049] Embodiment 9:
[0050] The larch was cut into wood chips with a length of 30 mm, a width of 30 mm, and a thickness of 3 mm; the cut wood was immersed in a 14% sodium hypochlorite solution, stirred at room temperature for 3 hours, and the wood was repeatedly washed with deionized water, and then freeze-dried; the delignified wood was immersed in a 6% KH560 solution (v / v, 95% ethanol solvent) and stirred at room temperature overnight, and then the unbound KH560 was washed with deionized water, and then freeze-dried again; placed in 50 mL of ethylenediamine, reacted at 65° C. for 10 hours, and after the reaction, the wood chips were washed with a large amount of deionized water; the wood chips were placed in a 50 mg / mL heparin sodium methanol solution and incubated for 24 hours, and then 30 mg of sodium borohydride was added and incubated for 12 hours. After the reaction, the wood chips were repeatedly washed with deionized water and freeze-dried to obtain a heparin affinity wood-based integral separation column.
Claims
1. A method for preparing a three-dimensional porous wood-based monolithic column, characterized in that: The stationary phase of the wood-based monolithic column uses wood as a skeleton, and uses chemical methods to treat and modify its pore surface, allowing its surface to be connected with functional ligands, and then placed in an empty chromatographic column for separation and purification of substances; The structural formula of the three-dimensional porous wood-based monolithic column is [W]-(A)-(B) Wherein, [W] is natural wood or delignified wood, (A) is an intermediate arm used to connect the wood and the functional ligand, and (B) is a functional ligand that can interact with the target substance through specific binding force or nonspecific binding force; Among them, (A) is a non-essential structure, and the whole column is presented in the [W] (B) structure; The intermediate arm includes silane coupling agent, glutaraldehyde, epichlorohydrin, dextran, agarose, cellulose, polyethylene glycol, and functional monomers, and is combined with hydroxyl or carboxyl groups on the surface of the inner pores of natural wood or delignified wood through chemical reaction, and the combination method includes direct modification (grafting-to) of small molecule compounds or macromolecular polymers, surface grafting polymerization (grafting-from), and monomer copolymerization grafting (grafting-through); Among them, functional ligands include affinity ligands, hydrophobic ligands, ion exchange ligands, chiral resolving ligands, and mixed mode ligands.
2. According to the method for preparing the three-dimensional porous wood-based monolithic column as described in claim 1, the wood is coniferous wood or broad-leaved wood, including natural wood or delignified wood.
3. According to the preparation method of the three-dimensional porous wood-based integral column described in claim 2, the delignified wood preparation method includes a hypochlorite method, a chlorite method, a sulfite method, a lignin in-situ modification method, and an enzyme treatment method; the degree of delignification of the delignified wood is that the wood can maintain its original three-dimensional porous structure.
4. According to the preparation method of the three-dimensional porous wood-based monolithic column described in claim 1, the silane coupling agent includes vinyl triethoxysilane (A-151), γ-aminopropyl trimethoxysilane (KH540), γ-aminopropyl triethyloxysilane (KH550), 3-glycidyloxypropyl trimethoxysilane (KH560), γ-methacryloxypropyl trimethoxysilane (KH570), and N-β-aminoethyl-γ-aminopropyl methyl dimethoxysilane (KH602).
5. According to the method for preparing a three-dimensional porous wood-based monolithic column as described in claim 1, the polyethylene glycol includes two-arm polyethylene glycol, four-arm polyethylene glycol, eight-arm polyethylene glycol, and branched polyethylene glycol, and its molecular weight is 120 to 100,000 KD.
6. According to the method for preparing a three-dimensional porous wood-based monolithic column as described in claim 1, the functional monomer refers to an unsaturated, cyclic or low-molecular compound containing two or more functional groups, including styrene, methylstyrene, acrylamide, methacrylamide, N-isopropylacrylamide, glycidyl methacrylate, butyl methacrylate, and N-allyldimethylamine.
7. The method for preparing a three-dimensional porous wood-based monolithic column according to claims 1-6, wherein the shape of the wood-based monolithic column is a cylinder, and the wood-based monolithic column is a whole piece of wood or a plurality of wood-based blocks stacked together.
8. According to the method for preparing the three-dimensional porous wood-based monolithic column described in claims 1-7, the wood-based monolithic column can be used for affinity chromatography, ion exchange chromatography, hydrophobic chromatography, normal phase chromatography, reverse phase chromatography, mixed mode chromatography, and chiral separation chromatography.
Citation Information
Patent Citations
L-phenylalanine analysis detection method based on molecular engram integral column
CN101487822A
Monolithic column, preparation method and application thereof
CN101537344A
Multifunctional cellulose-based material with chiral separation function and preparation method thereof
CN110841613A
Preparation method of chiral ZIF-8 (at) MXene / CA composite porous material
CN114870814A
Method for purifying protein using activated carbon
US20190211056A1
